Quantitative assessment of outer retinal layers and ellipsoid zone mapping in hydroxychloroquine retinopathy. Issue 1 (6th September 2018) - Ugwuegbu, Obinna; Uchida, Atsuro; Singh, Rishi P; Beven, Lucas; Hu, Ming; Kaiser, Stephanie; Srivastava, Sunil K; Ehlers, Justis P
Abstract : Background: To quantitatively assess outer retinal layers in eyes with hydroxychloroquine (HCQ) toxicity. Methods: A retrospective case–control study was performed to identify eyes with HCQ retinopathy/toxicity at Cleveland Clinic. A clinical diagnosis of HCQ retinopathy was made based on clinical and imaging features including the presence of parafoveal ellipsoid zone (EZ) loss on spectral-domain optical coherence tomography (OCT) and visual field defects. All participants underwent macular cube scan using the Cirrus HD-OCT (Zeiss, Oberkochen, Germany). Quantitative assessment of outer nuclear layer (ONL)/Henle fibre layer complex (HFL) metrics and EZ mapping were performed with a novel software platform and compared with age-matched controls. HCQ toxicity group was divided into three subgroups based on the severity. Results: There were 14 eyes from 14 patients in HCQ toxicity group (mean age 57.0±18.6 years), and 14 eyes from 14 subjects in age-matched control group (mean age 59.4±18.6 years). Multiple outer retinal parameters including ONL/HFL-EZ volume, parafoveal ONL/HFL-EZ thickness and EZ-retinal pigment epithelium (RPE) volume were significantly reduced in all HCQ toxicity subgroups (early, moderate and advanced toxicity) compared with controls. Semiautomated layer segmentation tool produced en face representation of EZ-RPE mapping and allowed unique visualisation of EZ attenuation in eyes with HCQ toxicity. The longitudinal analysis of HCQ toxicity group demonstrated progressive decline in some outer retinal parameters. Conclusion: HCQ toxicity resulted in significant outer retinal layer volumetric thinning compared with controls. Quantitative assessment of outer retinal parameters and EZ mapping on SD-OCT may become a useful biomarker to identify and monitor HCQ toxicity.